Gunungapi aktif di Indonesia / Sari B. Kusumayudha; penyunting, Ipung Kandri K, Arum P. Mayasari - SARI B. KUSUMAYUDHA , 1956-; Ipung Kandri K; Arum P. Mayasari (Citra Aji Parama, 2009)
iv, 44 hlm. : ilus. ; 25 cm.